Design and Construction of an IPL Payment Monitoring Information System Using a Website-Based Agile Method (Case Study: Situ Indah Kedaung Sawangan) - Rahmat Hartono; Chairul Anwar (Jurnal Teknologi Informatika dan Komputer, 2026)
The rapid advancement of information technology has accelerated digital transformation in various sectors, including housing community administration. Advances in information technology over the past few decades have transformed data management patterns across various sectors, including small-scale organizations such as housing management. Administrative digitization has become a crucial need to improve the speed, precision, and accuracy of information processing. Web-based information systems are a widely used solution because they integrate data recording, storage, and reporting processes in a single, easily accessible platform. The management of the Residential Property (IPL) at the Situ Indah Kedaung Sawangan Housing Complex is still carried out using conventional methods, resulting in inefficiency, data inaccuracy, and limited financial transparency. The manual recording process causes data fragmentation, complicates payment monitoring, and increases the risk of administrative errors. This study aims to design and develop a web-based IPK Payment Monitoring Information System that integrates resident data management, billing records, payment transactions, reporting, notifications, and regulatory management into a centralized platform. The system was developed using an Agile methodology, emphasizing iterative and collaborative development to ensure alignment with user needs. The results of the study show that the implemented system improves administrative efficiency, accelerates the monitoring and reporting process, and increases transparency and accountability in housing financial management through real-time access to information.